2022
DOI: 10.1159/000525539
|View full text |Cite
|
Sign up to set email alerts
|

How I Treat Localized Soft Tissue Sarcomas: Update on Diagnosis, Risk Stratification, and Treatment

Abstract: Background: Adult-type soft tissue sarcomas (STS) are rare tumors representing about 1% of all adult malignant tumors. Their extreme histological heterogeneity places them among the most challenging fields of diagnostic pathology. The variability of clinical and prognostic presentation between the various histotypes reflects the different management that should be followed on a case-by-case basis. These features make soft tissue sarcomas the case in point of how important it is a centralized and multidisciplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Previous research has found that tumors most commonly arise in the tubular bones of the extremities (46%), mostly in the lower extremities, followed by the pelvis (25%), trunk comprising ribs and spinal trunk (22%), and other locations (6%) [ 1 ]. The 5-year overall survival (OS) rate for patients with localized ES has grown to 65%, due to the use of surgery, chemotherapy, and radiation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that tumors most commonly arise in the tubular bones of the extremities (46%), mostly in the lower extremities, followed by the pelvis (25%), trunk comprising ribs and spinal trunk (22%), and other locations (6%) [ 1 ]. The 5-year overall survival (OS) rate for patients with localized ES has grown to 65%, due to the use of surgery, chemotherapy, and radiation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%